ANALYSIS OF STUDENTS’ MATHEMATICAL COMMUNICATION ABILITY BY USING COOPERATIVE LEARNING TALKING STICK TYPE - Dwi Maulida Sari (IKIP Siliwangi and I-MES, 2017)
This research aims to describe the students’ mathematical communication ability by using cooperative learning talking stick type. This research conducted at one of junior high school in Asahan-North Sumatera- North Sumatera. This research used posttest experimental class design as the method to obtain data. The indicators used to measure mathematical communication ability in this research arranged in three, as follows: 1) the ability of explaining a mathematical problem into figure; 2) the ability to explain mathematical problem situations by own words; 3) the ability of stating a mathematical problem in writing into mathematical models and doing calculation to solve the problem. The result found from this research is there are the differences in the students’ way of answering the problem even though the learning model and the instrument used is same.